2012
DOI: 10.3109/15412555.2012.692000
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Computed Tomography in Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-analysis

Abstract: The current meta-analyses suggest that quantitative measures of CT may be useful to diagnose COPD. Developed CT technology may improve the accuracy of diagnosis. Further studies assessed diagnostic performance of CT are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Several studies reported that D Lco correlated stronger with emphysema in the upper lobes ( 23 ), while, in contrast, there are studies that reported the opposite – that PFT values, especially D Lco, correlated stronger in the lower lobes ( 29 ). In our study, the moderate negative correlation between the right upper lobe and D Lco was the strongest compared with other lobes ( r = –0.61, p < 0.000).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies reported that D Lco correlated stronger with emphysema in the upper lobes ( 23 ), while, in contrast, there are studies that reported the opposite – that PFT values, especially D Lco, correlated stronger in the lower lobes ( 29 ). In our study, the moderate negative correlation between the right upper lobe and D Lco was the strongest compared with other lobes ( r = –0.61, p < 0.000).…”
Section: Discussionmentioning
confidence: 98%
“…However, Marshall et al (34) attributed the failure to exhibit a significant correlation between CT and MR normalized S 0 to the inaccuracy of S 0 measurement and also speculated that normalized S 0 maps would yield a better performance than raw MR signal intensity images in the investigation of diseased lungs. Our approach of mapping lung THORACIC IMAGING: MR Quantitative Equilibrium Signal Mapping Zhang et al (sensitivity, 83%; 95% confidence interval: 73%, 89%; specificity, 87%; 95% confidence interval: 70%, 95%) for a diagnosis of COPD (36).…”
Section: Discussionmentioning
confidence: 99%
“…It is now possible to perform a more objective evaluation using tools and software to carry out measurements such as the emphysema index (EI), which defines the relation between the volume of emphysema and total lung volume after a three-dimensional reconstruction. Other indicators include the pixel index (PI), defined as the percentage of pixels with an attenuation of <−900 UH, as well as the EI in expiration (EIex), PI in maximum expiration (PIex), and the pulmonary blood flow (BF) 25,26 . The sensitivity of the EI in the HRCT is 0.80 (95% confidence interval [CI], 0.74-0.84), while when the tomographic signs (EI, PIex, EIex, and BF) are combined, the sensitivity for detecting emphysema rises up to 0.87 (95% CI, 0.64-0.96) 25 .…”
Section: Ct Scanning and Diffusing Capacity To Identify Emphysema Andmentioning
confidence: 99%
“…Other indicators include the pixel index (PI), defined as the percentage of pixels with an attenuation of <−900 UH, as well as the EI in expiration (EIex), PI in maximum expiration (PIex), and the pulmonary blood flow (BF) 25,26 . The sensitivity of the EI in the HRCT is 0.80 (95% confidence interval [CI], 0.74-0.84), while when the tomographic signs (EI, PIex, EIex, and BF) are combined, the sensitivity for detecting emphysema rises up to 0.87 (95% CI, 0.64-0.96) 25 . In comparison with inspiration, CT measurements in expiration are tightly correlated with airflow obstruction; however, this exposes the patients to additional radiation 26 .…”
Section: Ct Scanning and Diffusing Capacity To Identify Emphysema Andmentioning
confidence: 99%